A versatile setup for the observation of different quantum phenomena (2017)
We propose an experimental setup capable of constructing and monitoring quantum evolutions. In addition, applications that use the proposed scheme to implement quantum random walks and the quantum Zeno effect are briefly explained, showing this way both the capabilities and versatility of our scheme. Finally, the setup is arranged to establish a configuration in which, by means of weak measurements, a measurement of non-commuting operators can be achieved.